Computational Fluid Dynamics Modeling of Sweep Gas Flow Rate-Dependent Carbon Dioxide Removal in Oxygenators - Keira Askew; Julia Rizzo; Lei Fan; Ge He (Fluids, 2025)
Computational fluid dynamics (CFD) models have been widely used to evaluate the hydrodynamic and gas exchange performances of oxygenators, which are crucial in supporting patients with lung diseases or failure. However, while CFD models have been effective in analyzing oxygen transfer, they have not adequately addressed the experimentally demonstrated effects of varying sweep gas flow rates on CO2 removal. This is a critical gap, as sweep gas flow directly influences the CO2 transfer efficiency in oxygenators. To fill this gap, we extend our previously developed 1D mathematical model into a 3D computational framework to predict both blood pressure drops and the rates of oxygen and CO2 transfers in oxygenators. The comparison between our model predictions and experimental data validates the model’s capability in capturing the overall trends in CO2 transfer/removal rates under different sweep gas flow rates. The results also demonstrated that our model can predict CO2 removal more accurately, particularly in scenarios where adjusting the sweep gas flow rate is essential for optimizing the oxygenator performance.